Application of Fuzzy TOPSIS MADM approach in ranking & underlining the problems of plywood industry in India. Issue 1 (31st December 2016) - Mittal, Kapil; Chandra Tewari, Puran; Khanduja, Dinesh; Kaushik, Prabhakar
Abstract: The manufacturing of plywood consists of simple procedural steps, but the range of problems associated with the plywood manufacturing industries, especially in the case of small-scale industries (SSI), is large. This paper describes the major problems faced by the plywood SSIs along with their cause and the ultimate effect, i.e. pruning the profits. Many cogent tools and techniques are present for the task, but an attempt has been made to apply multiple attribute decision-making (MADM) approach in ranking the problems in order of their extent on the basis of various parameters. Some suggestions for the improvement purposes have also been made to overcome the top-ranked problem. The study is the first of its type in a plywood industry, although same can be applied to other similar small-scale cluster industries like steel, textile, pharmaceutical, and automobile.